Bullous pemphigoid and cholestatic hepatitis associated with Castleman’s disease - Murat ÖKSÜZ; Yılmaz ERGÜN; Ülkü ADAM; Gülfiliz GÖNLÜŞEN; Y. Fatih IŞIKSAL; Melek ERGİN and Fatin KOÇAK and Bahri ABAYLI and Hikmet AKKIZ and Ayşe AKMAN (Turkish Journal of Gastroenterology, 2019)
-